Determination of the Factors Preventing Students of the Faculty of Sports Sciences from Participating in Recreational Activities: Ondokuz Mayis University Sample (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
The purpose of this study is to examine the factors which prevent the students of Faculty of Sport Sciences fromparticipating in recreational activities in terms of some variables.A total of 275 (183 men, 92 women) randomly chosen students studying at Ya?ar Do?u Faculty of Sport Sciences participated in the study voluntarily. “Leisure Constraints Questionnaire” developed by Alexandris and Carroll (1997)adapted to Turkish by Karaküçük and Gürbüz (2007) was used as the data collection tool. The data obtained wereanalyzed with SPSS 21 package program. Kolmogrov test was used to find out whether the data were normally distributed and the data were found to be normally distributed. The data were analyzed with frequency analysis, t test and Anova test in independent samples and the Bonferroni test was used to analyze the difference between groups.The factors which prevented students from participating in recreational activities showed significant differences in“individual psychological” subscale and total scores in terms of the variable of age and in “facilities/services andaccessibility” subscale in terms of gender (p